2022
DOI: 10.1038/s41386-022-01283-8
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-blunted cortisol response to stress is associated with increased negative mood and wanting of social reward

Abstract: Animal research suggests a central role of the μ-opioid receptor (MOR) system in regulating affiliative behaviors and in mediating the stress-buffering function of social contact. However, the neurochemistry of stress-related social contact seeking in humans is still poorly understood. In a randomized, double-blind, between-subjects design, healthy female volunteers (N = 80) received either 10 mg of the µ-opioid agonist morphine sulfate, or a placebo. Following a standardized psychosocial stress induction, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 74 publications
1
7
3
Order By: Relevance
“…Moreover, and in line with the early findings by Beecher et al. [13], increased negative affect has been reported after morphine [19], oxycodone [16] and remifentanil [20] administration. Nevertheless, opioid analgesics are routinely used clinically with the aim of dampening subjective and physiological stress, e.g.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, and in line with the early findings by Beecher et al. [13], increased negative affect has been reported after morphine [19], oxycodone [16] and remifentanil [20] administration. Nevertheless, opioid analgesics are routinely used clinically with the aim of dampening subjective and physiological stress, e.g.…”
Section: Introductionsupporting
confidence: 82%
“…While the opioid analgesics hydromorphone, morphine and buprenorphine have been shown to block cortisol responses to stress induction, none relieved subjective anxiety [14,15,19]. Moreover, and in line with the early findings by Beecher et al [13], increased negative affect has been reported after morphine [19], oxycodone [16] and remifentanil [20] administration.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Finally, regardless of the drug group, in the ROI analysis we observed that wanting-related activity in the NAc and medial OFC was mainly elicited by the anticipation of food rewards, but not touch rewards, suggesting possible differences in neuroanatomical circuitry underlying social and nonsocial reward processing. Social touch is considered a reward as it triggers approach behavior (wanting)-for example, individuals are willing to work to obtain it-and its experience is commonly associated with pleasure (liking), expressed as subjective ratings or positive facial expressions (e.g., Korb, Götzendorfer, et al, 2020;Løseth et al, 2019;Massaccesi et al, 2021Massaccesi et al, , 2022Mayo et al, 2018;Perini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, regardless of the drug group, in the ROI analysis we observed that wanting‐related activity in the NAc and medial OFC was mainly elicited by the anticipation of food rewards, but not touch rewards, suggesting possible differences in neuroanatomical circuitry underlying social and nonsocial reward processing. Social touch is considered a reward as it triggers approach behavior (wanting)—for example, individuals are willing to work to obtain it—and its experience is commonly associated with pleasure (liking), expressed as subjective ratings or positive facial expressions (e.g., Korb, Götzendorfer, et al, 2020 ; Korb, Massaccesi, et al, 2020 ; Løseth et al, 2019 ; Massaccesi et al, 2021 , 2022 ; Mayo et al, 2018 ; Perini et al, 2015 ). Nevertheless, prior neuroimaging research showed that social touch is commonly associated with activity in the insula, secondary somatosensory cortex, and temporal regions, while activity of reward‐related brain regions, like the OFC and the NAc, has been less consistently reported (e.g., Bjornsdotter et al, 2014 ; Gordon et al, 2013 ; Sailer et al, 2016 ; Sander & Nummenmaa, 2021 ).…”
Section: Discussionmentioning
confidence: 99%